Neotypification and redescription of Amanita preissii (Basidiomycota), and reconsideration of the status of A. griseibrunnea - Davison, Elaine; Giustiniano, D.; McGurk, L.; Watkin, E.; Bougher, N. (Department of Environment and Conservation, WA, 2017)
Amanita preissii (Fr.) Sacc. is redescribed. Re-examination of collections of A. griseibrunnea O.K.Mill. show that they do not differ significantly from A. preissii and the two species are combined. This species is common in the Perth IBRA subregion. Sequence data from the nuclear ribosomal internal transcribed spacer (ITS) region, 28S nuclear ribosomal large subunit rRNA (28S) region, RNA polymerase II (RPB2) region, β-tubulin region and translation elongation factor 1-α (EF1-α) region have been deposited in GenBank.